Behaviour of hot mix asphalt incorporating untreated and treated waste cooking oil - Wan Azahar, Wan Nur Aifa; Kasim, Norhidayu; Ismail, Norfarah Nadia; Putra Jaya, Ramadhansyah; Hainin, Mohd Rosli; Masri, Khairil Azman; Bujang, Mastura; Al-Saffar, Zaid Hazim (Springer, 2021)
The recyclability of waste cooking oil (WCO) as rejuvenator for aged asphalt mixture improved the serviceability of pavement itself. Currently, the researcher is exploring the new potential of WCO as modifer for binder modifcation. However, the issue of compatibility properties in the modifcation of binder with WCO arises since the poor mechanical performance of asphalt mixture is globally recorded thus refected the weakness of adhesion bonding inside the pavement material. Basically, the superior mechanical performance of asphaltic concrete exhibited good adhesion bonding between binder-aggregates interaction in bituminous mixture. In fact, the potential of high adhesiveness binding properties is afected by the chemical theory which is mostly related to the polarity factor. Therefore, it is vital to conduct the chemical analysis and microstructure observation to obtain a comprehensive understanding of the polar group behaviour for the internal structure in pavement material that infuencing the adhesion performance for the structural arrangement material in the mixture. Therefore, excellent adhesion is capable of improving mechanical performance of Hot Mix Asphalt (HMA). The identifcation of chemical composition for polarity group determination was identifed by using Gas Chromatography-Mass Spectrometry (GC–MS). Meanwhile, the adhesiveness measurement between binder-aggregate interactions in the mixture was observed with Field Emission Scanning Electron Microscope (FESEM) which physically resulting in mechanical performance by conducting resilient modulus test, dynamic creep test and indirect tensile strength (ITS) test. Results showed that the incompatibility characteristic is revealed between untreated WCO and conventional binder (PEN 60/70) based on the identifcation of polar and non-polar compounds interaction. Thereby, exhibits the existence of gap and void structure arrangement in HMA through FESEM visualization hence afecting the poor mechanical strength of asphalt mixture.